(untitled) (Sains Humanika, 2023)
Industry 4.0 shaped Society 5.0 which focused heavily on people and gave equal merit to economic development and the resolution of public issues through the utilization of a system that immensely incorporates both cyber and reality. Cyberspace such as media social is heavily used and allows users to become completely anonymous which ultimately gave birth to a new type of crime such as identity manipulation. The advancement of technology has made it simpler for an average person to change the mannerisms, appearance, and physical makeup of another human being, which is often done without their knowledge. When it comes to identity manipulation done by an individual or law enforcement even for a good reason, arguments may ensue. Is it wrong for an individual or law enforcement to pull off identity manipulation in order to lure internet predators or to deter crime by arresting the perpetrator before the crime happened? Isn’t this act can be viewed as the act of deceiving somebody into violating the law? These examples of formal arguments about the appropriate course of action that needs to be taken when confronted with a moral issue are known as ethical theories. The aim of this paper is to discuss the three different Ethical Theories including Kantianism, Utilitarianism, and Devine Command Theory on social media identity manipulation in the context of Industry 4.0 and Society 5.0 using secondary data and information acquired from the literature review. Finally, we can reach the conclusion that what is ethically right in societies should be respected and that people should never be used for another’s self-gain.